Respuesta :

Answer:

m=-29/3 and n=65/3

Step-by-step explanation:

The given system has equations:

3m+3n=36

8m+5n=31

Multiply the top equation by 5 and bottom equation by 3 to get:

15m+15n=180

24m+15n=93

Subtract the top equation from the bottom equation to get:

9m=-87

Divide both sides by 9

[tex]m = - \frac{29}{3} [/tex]

We substitute this value into the first equation to get:

[tex]3( - \frac{29}{3} ) + 3n = 36[/tex]

[tex]3n = 36 + 29[/tex]

[tex]3n = 65[/tex]

[tex]n = \frac{65}{3} [/tex]

A N S W E R

M = - 21 / 3

N = 39 / 3